2018
DOI: 10.1016/j.athoracsur.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Early Surgery on Clinical Outcomes After Degenerative Mitral Valve Repair

Abstract: Early surgical intervention for severe degenerative mitral regurgitation before symptoms, atrial fibrillation, and ventricular dysfunction are associated with excellent clinical outcomes. Besides complexity of leaflet lesion and repair quality, surgical timing also significantly affects repair durability. Early surgical intervention should therefore be recommended to reduce recurrent mitral regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Therefore, in patients with LV systolic dysfunction, including a decreased ejection fraction and increased LV dimension, the effects of MV repair might be compromised. In this study, our results showed that in patients with LV systolic dysfunction, the incidence of perioperative complications was low, and thirty-day mortality was comparable to that in previous studies and our early study [8]. Previous studies have shown that the perioperative mortality rate of MV repair in degenerative MR varies from 0.2 to 1.2% [1,6,9,10].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, in patients with LV systolic dysfunction, including a decreased ejection fraction and increased LV dimension, the effects of MV repair might be compromised. In this study, our results showed that in patients with LV systolic dysfunction, the incidence of perioperative complications was low, and thirty-day mortality was comparable to that in previous studies and our early study [8]. Previous studies have shown that the perioperative mortality rate of MV repair in degenerative MR varies from 0.2 to 1.2% [1,6,9,10].…”
Section: Discussionsupporting
confidence: 84%
“…We also found in our study that anterior leaflet prolapse and intraoperative residual mild MR were independent predictive factors for recurrent MR; however, in previous studies, patients with preserved LV systolic function constituted most of the patient cohorts. In our previous study [ 8 ], we found that recurrent MR was only 3% at 8-year during follow up for those who received early surgical intervention before the onset of guideline-based indications. Therefore, preoperative LV systolic dysfunction might be associated with recurrent MR. A dilated left ventricle with LV systolic dysfunction could lead to annular enlargement and apically displaced leaflets, which cause secondary MR.…”
Section: Discussionmentioning
confidence: 99%
“…The results of degenerative MV repair at our institution have been published previously; the overall hospital mortality for degenerative MV repair is 1.8%. 5 The operative details are provided in Table 2. The CPB and crossclamp times were not significantly different in the PMR and elective IMR subgroups, and the postoperative complications were comparable.…”
Section: Resultsmentioning
confidence: 99%
“…The techniques of MV repair for primary MR at our institution have been described in a previous article. 5 In the IE patients, we fully inspected the infectious lesions on the valve and surrounding tissue. First, we removed vegetations and infection foci.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of the results, at least in terms of survival, is strictly related to the presence of preoperative risk factors, as atrial fibrillation or pulmonary hypertension or reduced ejection fraction. It is indubitable that better results can be achieved when patients are operated on in an early phase, without the late consequences of the disease (13,14).…”
mentioning
confidence: 99%